Exploring and visualizing large-scale genetic associations by using PheWeb - Gagliano Taliun, Sarah A.; VandeHaar, Peter; Boughton, Andrew P.; Welch, Ryan P.; Taliun, Daniel; Schmidt, Ellen M.; Zhou, Wei; Nielsen, Jonas B.; Willer, Cristen J.; Lee, Seunggeun; Fritsche, Lars G.; Boehnke, Michael; et al. (Nature genetics, 2020)
The ability of investigators to explore their own data by alternating between these two view types, is an increasingly common feature of large-scale association analyses. [...]we developed PheWeb, an easy-to-use open-source web-based tool for visualizing, navigating and sharing GWAS and PheWAS results. The regional view (Supplementary Fig. 4) highlights that rs4975616 and several of its proxies are in the GWAS Catalog and are associated with various cancers (for example, lung cancer, pancreatic cancer and basal cell carcinoma), thus suggesting a broad role of the locus in cancer susceptibility. Interestingly, for the other top loci (both on chromosome 8), the regional and PheWAS views (rs2976384 in JRK and PSCA, Fig. 1b,c; rs10094872 near ???, Supplementary Figs. 6 and 7) distinctly convey that these loci are not associated with skin and lung cancers, but are instead associated with gastric and urinary traits such as duodenal ulcer, urinary tract infection and pancreatic cancer. [...]PheWeb is as useful as the data and results behind it, but we expect that these results will be much more useful when they are accessible.